A limited legacy effect of copper in marine biofilms. Issue 1 (15th August 2016) - McElroy, David J.; Doblin, Martina A.; Murphy, Richard J.; Hochuli, Dieter F.; Coleman, Ross A.
Abstract: The effects of confounding by temporal factors remains understudied in pollution ecology. For example, there is little understanding of how disturbance history affects the development of assemblages. To begin addressing this gap in knowledge, marine biofilms were subjected to temporally-variable regimes of copper exposure and depuration. It was expected that the physical and biological structure of the biofilms would vary in response to copper regime. Biofilms were examined by inductively coupled plasma optical emission spectrometry, chlorophyll-a fluorescence and field spectrometry and it was found that (1) concentrations of copper were higher in those biofilms exposed to copper, (2) concentrations of copper remain high in biofilms after the source of copper is removed, and (3) exposure to and depuration from copper might have comparable effects on the photosynthetic microbial assemblages in biofilms. The persistence of copper in biofilms after depuration reinforces the need for consideration of temporal factors in ecology. Highlights: Marine biofilms were subjected to regimes of copper exposure and depuration. Effects of these regimes on the physical and biological structure of biofilms were measured. Concentrations of copper remain high in biofilms after the source of copper is removed. Exposure to and depuration from copper might have comparable effects on biofilms. Results reinforce the need for temporal factors to have greater focus in ecology.